Improved methods of the contrast-enhanced ultrasound in patient with chronic viral hepatitis - A. V. Tikhankova; A. V. Borsukov; A. O. Buyeverov; V. V. Ivanov; Yu. V. Ivanov (Клиническая практика, 2019)
Rationale. The article presents the data obtained by an improved method of contrast-enhanced ultrasound (CEUS) in patients with chronic viral hepatitis.